Re-comparing of three different epidemic seasons of bronchiolitis: different prophylaxis approaches - Simonetta Picone; Adele Fabiano; Davide Roma; Federico Di Palma; Piermichele Paolillo (BMC, 2018)
Abstract During the last epidemic season of bronchiolitis (S2, years 2016-2017) we performed a single Centre analysis in inborn infant of 30+ 0-32+ 6 gestational age and age < 12 months who did not receive prophylaxis with palivizumab (PLV), in light of the current AIFA (Italian Drug Agency) guidelines restricting the time of the prophylaxis to those born < 30 weeks of gestational age. During that epidemic season, we observed a rising trend of bronchiolitis-related hospitalization and an increased rate of mechanical ventilation in preterm child compared to the previous one (S1, years 2015-2016) during which infants of this same gestational age received palivizumab (PLV) prophylaxis, according to the 2015 Italian Guidelines. In light of the revised AIFA guidelines (November 2017), allowing once again prophylaxis with PLV in infants of > 30 weeks gestational age, we decided to repeat our observation during the last epidemic season (S3, years 2017-2018), in order to compare ours infants of 30+ 0-32+ 6 gestational age with preterm of the same gestational age born in our unit in the previous seasons (S1 and S2), to evaluate the clinical impact of the different prophylaxis approaches. The new observation confirmed the clinical efficacy of PLV in this delicate group of newborns in preventing almost completely new episodes of bronchiolitis. Of the 6 newborns who developed bronchiolitis, 4 had received only a single dose of PLV, providing suboptimal protection, before the onset of bronchiolitis; furthermore 3 developed a mild form allowing to be treated at home.